Capital adequacy requirement risk-weighted capital ratio / Mohd Rashid Mahiddin - Mahiddin, Mohd Rashid (1992)
A new capital framework, formulated along the lines of the Basic Capital Accord was tabled for discussion during the 1988 annual conferences with each of the three groups of licenced financial institutions.